2004
DOI: 10.1002/bdd.386
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of nifedipine in Taiwanese

Abstract: To elucidate the pharmacokinetics of nifedipine in Taiwanese, a retrospective review of nifedipine bioequivalence studies completed in Taiwan in the past 5 years was conducted. A total of 198 healthy male volunteers were given a single dose of a 10 mg Adalat capsule as a reference drug after overnight fasting. Pharmacokinetic parameters derived from Adalat administration were calculated by non-compartmental analysis with the WinNonlin program. After oral administration of an immediate-release dosage form of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…3), although the C max obtained in this study was similar to that reported in the drug information for prescription [1]. The half-life obtained in this Mexican population is 3 h, which is slightly lower than that reported in references (4.0 h) [1] and suggesting that Mexican population may eliminate DPN faster than other populations, such as is suggested for other drugs and populations [12][13][14][15].…”
Section: Resultssupporting
confidence: 49%
See 1 more Smart Citation
“…3), although the C max obtained in this study was similar to that reported in the drug information for prescription [1]. The half-life obtained in this Mexican population is 3 h, which is slightly lower than that reported in references (4.0 h) [1] and suggesting that Mexican population may eliminate DPN faster than other populations, such as is suggested for other drugs and populations [12][13][14][15].…”
Section: Resultssupporting
confidence: 49%
“…Our rather simple analytical HPLC-UV method for determination of DPN in human plasma was demonstrated to be precise and accurate it can be successfully used in pharmacokinetic or bioequivalence studies and for continuous drug monitoring under a multi-dose administration regime. This pharmacokinetic data of DPN in Mexicans has not been previously reported, suggesting differences in pharmacokinetic profiles linked with ethnic genotype composition [12][13][14][15]. Finally, both oral formulations tested containing 25 mg of DPN and manufactured in Mexico are bioequivalent.…”
Section: Resultsmentioning
confidence: 48%
“…However, concentrations of even a low dose of an administered dihydropyridine (e.g. 10–20 mg) can approach micromolar levels with any one of several contributing factors, such as advanced age, use of H 2 -receptor antagonists and/or being of non-caucasian lineage (Renwick et al, 1988; Chien et al, 2004; Ahmad et al, 2009; Robertson et al, 1988; Kahn et al, 1991). As such, it has been postulated that dihydropyridines may act within the CNS of patients to affect these additional channels and receptors (Das et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the severity of the pathology of the PH between the two studies is different. Second, amlodipine has a longer half‐life 28,29 than nifedipine 30 (3.08 ± 1.61 vs 0.93–01.12 h, respectively). Both these factors may contribute to the differences in the effects between nifedipine and amlodipine in attenuating PH 28 …”
Section: Discussionmentioning
confidence: 99%